Characterization of virus-derived small interfering RNAs in Apple stem grooving virus-infected in vitro-cultured Pyrus pyrifolia shoot tips in response to high temperature treatment. Issue 1 (December 2016) - Liu, Juan; Zhang, XueJiao; Yang, YueKun; Hong, Ni; Wang, GuoPing; Wang, Aiming; Wang, LiPing
Abstract Background Heat treatment (known as thermotherapy) together with in vitro culture of shoot meristem tips is a commonly used technology to obtain virus-free germplasm for the effective control of virus diseases in fruit trees. RNA silencing as an antiviral defense mechanism has been implicated in this process. To understand if high temperature-mediated acceleration of the host antiviral gene silencing system in the meristem tip facilitates virus-derived small interfering RNAs (vsiRNA) accumulation to reduce the viral RNA titer in the fruit tree meristem tip cells, we used theApple stem grooving virus (ASGV)–Pyrus pyrifolia pathosystem to explore the possible roles of vsiRNA in thermotherapy. Results At first we determined the full-length genome sequence of the ASGV-Js2 isolate and then profiled vsiRNAs in the meristem tip of in vitro-grown pear (cv. 'Jinshui no. 2') shoots infected by ASGV-Js2 and cultured at 24 and 37 °C. A total of 7, 495 and 7, 949 small RNA reads were obtained from the tips of pear shoots cultured at 24 and 37 °C, respectively. Mapping of the vsiRNAs to the ASGV-Js2 genome revealed that they were unevenly distributed along the ASGV-Js2 genome, and that 21- and 22-nt vsiRNAs preferentially accumulated at both temperatures. The 5′-terminal nucleotides of ASGV-specific siRNAs in the tips cultured under different temperatures had a similar distribution pattern, and the nucleotide U was the most frequent. RT-qPCR analyses suggested that viral genome accumulation was drastically compromised at 37 °C compared to 24 °C, which was accompanied with the elevated levels of vsiRNAs at 37 °C. As plant Dicer-like proteins (DCLs), Argonaute proteins (AGOs), and RNA-dependent RNA polymerases (RDRs) are implicated in vsiRNA biogenesis, we also cloned the partial sequences ofPpDCL2, 4, PpAGO1, 2, 4 andPpRDR1 genes, and found their expression levels were up-regulated in the ASGV-infected pear shoots at 37 °C. Conclusions Collectively, these results showed that upon high temperature treatment, the ASGV-infected meristem shoot tips up-regulated the expression of key genes in the RNA silencing pathway, induced the biogenesis of vsiRNAs and inhibited viral RNA accumulation. This study represents the first report on the characterization of the vsiRNA population in pear plants infected by ASGV-Js2, in response to high temperature treatment.